Estratégia de enriquecimento para isolamento de microrganismos com potencial para degradação de aflatoxina B1 - Suzuki, Suelen Luiz Gibellato (2019)
Mycotoxins are secondary metabolites produced by filamentous fungi that have toxigenic effects on humans and animals. Considering the contamination of food - especially grains - by this toxin, the need to produce safe food, minimize economic losses related to food contamination, and the absence of effective removal strategies for these contaminants, it is necessary to research and develop processes that effectively act on this issue. In this work the objective was to recover and identify microorganisms with aflatoxin B1 (AFB1) degradation potential from soil and corn (Zea mays) samples submitted to enrichment in coumarin medium, since aflatoxins are derived from difuranocoumarin. Five samples of soil cultivated with soybeans with a recent aflatoxin contamination history, and four samples of corn grains out of quality standards were collected, which were cultivated in a liquid medium containing coumarin as sole carbon source. Enrichment was conducted for six weeks, and at the end of the period only one isolate (S1) with growth capacity in coumarin medium was identified. Isolate S1 was identified by morphological and molecular analysis, which indicated that it is an organism of the genus Paecilomyces sp. In addition, the growth potential of the fungus in coumarincontaining medium as sole carbon source and in nutrient broth added from AFB1 was verified. Further studies should be conducted to evaluate its degradation capacity of AFB1 and to investigate the biotechnological application potential of this isolate